Disassembly of micelles in nanoscopic space to prepare concentric nanotubes with variable hydrophobic interiors - Das, Chayanika; Krishnamoorthy, Kothandam (Chemical Communications, 2014)
Nanotubes with variable hydrophobic interiors were prepared by disassembling anionic micelles in the inner walls of positive charge bearing conjugated polymer nanotubes.